A Comparative Study on Nutritional Status of Urban and Rural Early Adolescent School Girls of West Bengal, India - Maiti, S; Ali, KM; De, D; Bera, TK; Ghosh, D; Paul, S (Journal of Nepal Paediatric Society, 2011)
Objectives: Adolescents remain largely neglected and especially girl from a deprived section in our society. The present study is an attempt to evaluate the nutritional status of early adolescent school girl from rural and urban areas. The study was, therefore, carried out to determine and compare the nutritional status of adolescent girl attending urban and rural secondary schools in Paschim Medinipur district of West Bengal, India. Methods: Cross-sectional data based on anthropometric measurements (height, weight) was collected from 2545 girls aged 10 to 14 years attending Govt. approved schools in Kharagpur town and Dantan-II block. The nutritional status has been assessed with the help of some anthropometric indices. The weight and height were recorded for each girl, and converted to nutritional indices (weightfor- age, height-for-height, BMI-for-age Z-scores of the National Center for Health Statistics reference standrads). Results: The mean nutritional indices (underweight, stunting and thinness) were found to be much lower among the rural girl than urban girl. The overall prevalent rates of underweight, stunting and thinness were 27.9%, 32.5% and 20.2% respectively. In the rural area these were 35.4%, 35.7% and 26.3%, while in the urban they were 19.6%, 29.0% and 13.6% respectively. Conclusions: The present study shows that undernutrition constituted major health problems among early adolescent school girls in rural areas of India. Hence, the special emphases are needed to formulate various developmental and healthcare programmes for rural communities to prevent undernutrition. Key words: Nutritional status; Early Adolescent girls; Rural; Urban DOI: http://dx.doi.org/10.3126/jnps.v31i3.5352 J Nep Paedtr Soc 2011;31(3):169-174